Homecoming - Portes, Gil M. (Regal Home Video., 2005)
Award-winnig actresses Elizabeth Oropesa and Alessandra De Rossi play a mother and daughter caught in a heart-wrenching homecoming. de Rossi comes home after five years of hard work as a nurse in Canada eager to be reunited with her family and sweetheart, whom she intents to marry. Oropesa sees in her daughter the hope of a brighten and more prosperous tomorrow. The entire town welcome De Rossi home with pomp and circumstance, as if she was a heroine. But then, fate has other plans for her. She has contracted the SARS virus and unknowingly brings it home with her. Oropesa is devastated upon learning that her only daughter her hope for a better life is afflicted with the infectious disease that has caused panic around the world. The entire town comes to grips with the consequences of the tragic turn of events.